Study on the composition of municipal solid waste in Mahkota Aman commercial area - Wan Khairul Azizi, Wan Dris (2012)
Municipal Solid Waste (MSW) is anything that been consume and discards from human's activities on daiJy basis. These waste also known as trash, garbage, refuse, and rubbish. Increasing of MSW production in commercial is one of government concern, especially in Kuantan. In order to reduce and handle the MSW, suitable methods must be chose for their efficiency and effectiveness. This research was focus on solid waste composition and solid waste generation rate in Mahkota A.man commercial area. The commercial premise divided into three categories; public, product, and service with total 20 participants. For this study, two methods of data gathering were applied; on site sampling involving weigh and segregate solid waste generated, and questionnaire distribution. On site sampling Based on the study,solid waste generation rate were dominated by product type premise at 4.77kg/units.day from 10 units participants. Compare to J.77.kg/unit.day by public type premise (2 units), and service type premise generation rate were 0.96kg/unit.day (8 units). The relationship between solid waste composition and solid waste generation is based on type of the premise. Each premise generated different type of waste with different generation rate.